Friedman tongue position and cone beam computed tomography in patients with obstructive sleep apnea. Issue 5 (22nd August 2017) - Harvey, Rebecca; O'Brien, Louise; Aronovich, Sharon; Shelgikar, Anita; Hoff, Paul; Palmisano, John; Stanley, Jeffrey
Abstract : Objective: Evaluate the correlation between Friedman Tongue Position (FTP) and airway cephalometrics in patients with obstructive sleep apnea (OSA). Study Design: Retrospective review of adult patients with OSA undergoing Cone Beam Computed Tomography (CBCT). Methods: Collected data included age, sex, body mass index, apnea hypopnea index, FTP, and airway cephalometric parameters. Data analyses were performed using ANOVA, dichotomous t‐testing, and linear regression. Results: 203 patients were included in the analysis. (M:F 132:71). The mean posterior airway space (PAS) was inversely correlated ( p  = 0.001, r =.119) with higher FTP grades with means of 12.3 mm, 7.9 mm, 6.6 mm, and 4.3 mm, I‐IV respectively. Minimal cross‐sectional area for patients with FTP I‐IV was 245.7, 179.8, 137.6, and 74.2 mm, 2 respectively ( p  = 0.002, r  = .095). Mean hyoid‐mandibular plane (H‐MP) for FTP I‐IV was 20.6 mm, 20.4 mm, 24.7 mm, and 28.9 mm respectively. No statistically significant difference between H‐MP values when comparing patients with FTP I or II ( p  = 0.22). There were statistically significant differences when these two groups were individually compared to FTP III and IV ( p  = 0.002). Linear regression analysis confirmed an independent association between FTP and PAS (β = −2.06, p  < 0.001), minimal cross‐sectional area (β = −45.07, p  = 0.02), and H‐MP (β = 3.03, p  = 0.01) controlling for BMI, age, AHI, and sex. Conclusions: Use of FTP is supported by objective CBCT cephalometric results, in particular the PAS, minimal cross‐sectional area, and H‐MP. Understanding the correlation between objective measurements of retroglossal collapse should allow Otolaryngologists to more confidently select patients who may require surgery to address the retroglossal area, particularly when the ability to perform cephalometric analysis is not possible Level of Evidence: 4.